2022
DOI: 10.1039/d1nj06072d
|View full text |Cite
|
Sign up to set email alerts
|

Polyamidoxime grafting on ultrahigh-strength cellulose-based jute fabrics for effectively extracting uranium from seawater

Abstract: Uranium resources in the ocean are very rich, and it is an ideal substitute for the increasingly depleted terrestrial uranium mines. Hence, it is urgently needed to develop absorbents simultaneously...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The high K d values suggested that the GPAA membranes had good affinity with uranyl ions. 35 Furthermore, to obtain the adsorption capacity, a series of GPAA membranes were separately immersed in aqueous solutions with uranium concentrations varying from 0 to 50 ppm. The adsorption isotherm curve of equilibrium adsorption capacity ( q e ) versus equilibrium concentration ( C e ) was presented (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The high K d values suggested that the GPAA membranes had good affinity with uranyl ions. 35 Furthermore, to obtain the adsorption capacity, a series of GPAA membranes were separately immersed in aqueous solutions with uranium concentrations varying from 0 to 50 ppm. The adsorption isotherm curve of equilibrium adsorption capacity ( q e ) versus equilibrium concentration ( C e ) was presented (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The multifaceted advancements involve coordination between the uranium and the chelating sites; adsorbent characterization; computer-based ligand simulations, kinetics, and thermodynamic model fittings; and analysis of various parameters including the pH, contact time, adsorbent regeneration, elution efficiency, cost, and environmental sustainability . Recently a bundle of literature emerged from China that covers special metal–organic frameworks, inorganic–organic composites, a graphene oxide/amidoxime hydrogel, amidoxime functionalized carbon nanofibers, and ultrahigh molecular weight polyethylene to enhance bulk mechanical robustness. …”
Section: History Of Uranium Extraction From Seawatermentioning
confidence: 99%
“…Many methods are used to convert PAN into PAO, NH 2 OH amidoximation is the most classic method. [27][28][29][30][31] NH 2 OH amidoximation technique includes homogeneous and heterogeneous methods, which were react in organic solvents [31][32][33] and in aqueous solutions, 28,34 respectively. Organic solvents used in the homogeneous method result in environmental pollution and high cost, which dramatically reduces the comprehensive competitiveness of PAO in U(VI) extraction.…”
Section: Introductionmentioning
confidence: 99%
“…According to the R 2 values in Table S6, † the Langmuir model was more suitable to describe the adsorption process than the Freundlich model, demonstrating that adsorbed U(VI) was chemisorbed and formed a single layer on the KMnO 4 @PAO surface. [26][27][28] Aer the addition of KMnO 4 , the adsorption capacity is signicantly increased. This means that except PAO, the manganese related compounds in KMnO 4 @PAO can also recover U(VI), which can signicantly solidify U(VI) in acidic solutions.…”
mentioning
confidence: 99%